Conversation: The challenges of teaching in a "nano department". (July 2017) - Wagoner, Bryan; Gummer, Natalie; Rein, Nathan; Thompson, Curtis L.; Czander, Giovanna; Peterfeso, Jill; Pryor, Adam
Abstract: A panel at the 2016 American Academy of Religion conference staged, taped, transcribed, and edited this conversation about the challenges and opportunities of teaching in a "nano department" – an undergraduate religion or religious studies department (or combined religion and philosophy department) with only one, two, or three faculty members. Two things quickly become evident: one is the impossibility of coverage of the full religious studies curriculum, and the other is the necessity for collaboration with other departments. Neither of these is unique to nano departments, but there exists an intimacy between students and faculty in small departments, a necessary freedom to rethink the place of the study of religion in the liberal arts curriculum, and a disruptive value in what can be critiqued and contributed from a marginalized position. Arguably, nano departments are the canaries in the academic coal mine, charting the future of the humanities that cannot be discerned from the vantage point of Research‐1 contexts.